The problems of effectiveness in the Environmental Impact Assessmente in Costa Rica and its consequences for Geological Management - Astorga-Gättgens, Allan (2016)
This document presents the results of a process of technical review of nearly 60 records of environmental impact assessment (EIA) carried out in recent years as part of the course of Environmental Geology I. The main problems detected and most common indicated in most records. This concludes that there are serious problems in implementing existing procedures and current technical tools, by both environmental consultants and the “Secretaría Técnica Nacional Ambiental” (SETENA). To this situation, the environmental management consultant geologist is not the exception, reason why, it is necessary that the above professionals mentioned are aware of the severe legal consequences involved. Finally, this paper proposes five key solutions to correct and improve the serious efficiency problem of the EIA system, which has brought the country to a condition of unsustainable development.